Psychological testing history, principles, and applications - Gregory, Robert J. (Allyn and Bacon, 1996)
In addition to customary coverage of traditional topics and instruments, the author provides detailed presentations for several topics not always found in other textbooks. These topics include: history of psychological testing, early uses and abuses of intelligence, neuropsychological foundations of ability, factor analysis, assessment of learning disabilities, consumer assessment, environmental assessment, and courtroom testimony.